Organizational communication competence of public secondary school principals through utilizing WhatsApp - Neiroukh, Nader; Ansari, Abdel Afu; Dalu, Rida Abu; Khlaif, Enas; Barahmaeh, Dua’a; Zubeidi, Jamal; Shtayeh, Bilal; Daher, Wajeeh (Frontiers in Education, 2024)
Introduction: Effective communication is the heart of any organization. It is associated with employees’ job satisfaction and productivity and therefore, is responsible for the institution’s continuity and prosperity. In educational institutions, communication has been undergoing swift and significant changes that affected not only instructional strategies, but also administrative dimensions. The need for instant and precise information made digital mediums indispensable for school administration that helps in planning, following up, executing, and evaluating short-term and long-term goals. Since the start of the 21st century, a multitude of smartphone applications have surfaced, all designed to enhance communication. WhatsApp is one of the applications that stands as the most popular medium, which is widely spread and used on personal as well as professional basis. The question at hand is whether employing WhatsApp as a communication tool within educational institutions can effectively contribute to the development of communication competence, encompassing aspects such as communication motivation, communication knowledge, and communication skills. Methods: Based on the indicators used to measure communication competence in institutions, this qualitative study elicited relevant information through semi-structured interviews from 14 different government secondary school principals in Jerusalem and the West bank about the approach principals employ WhatsApp to achieve competence. Results: The results of the study show that indicators of communication competence are achieved through the use of WhatsApp.